CLASSIFICATION OF SPORTS GAMES - A.Mukhidinov; Sh.Tillaev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Sport has a special impact on the overall development of the individual, promotes the formation of life skills and abilities, promotes spiritual, moral and intellectual growth, and strengthens the personality, such as courage, will, spiritual refreshment. Mutual respect, friendship fosters a sense of solidarity, mutual assistance, nobility, honesty, a spirit of celebration, etc. are the most important qualities of the sport.